EFEKTIVITAS METODE PEMBELAJARAN PEER-ASSISTED LEARNING (PAL) TERHADAP PENGETAHUAN TINDAKAN PEMASANGAN INFUS - Syafrinanda, Virginia; Rihiantoro, Tori; Fatonah, Siti (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2025)
Background: One of the basic skills possessed by nursing students is the act of inserting an IV. The act of inserting an IV is one of the basic skills that prospective nurses need to know in meeting patient needs. Efforts to improve student knowledge through the peer assisted learning method which is a method of learning between peers and helping each other to learn. Purpose: to assess the level of student knowledge in the act of inserting an IV through the PAL method Methods: This study uses a pre-experimental research design in the form of a